Transesterification Reactions Catalyzed by a Recyclable Heterogeneous Zinc/Imidazole Catalyst. Issue 15 (31st May 2016) - Nakatake, Daiki; Yazaki, Ryo; Matsushima, Yoshimasa; Ohshima, Takashi
Abstract: We report the development of a universal and recyclable heterogeneous zinc/imidazole catalyst. The catalyst is recoverable through simple filtration and can be reused at least five times, retaining its catalytic activity. Leached zinc species were not responsible for the observed catalysis based on the hot filtration test and ICP‐MS analysis. The heterogeneous zinc catalyst also promotes chemoselective transesterification over amidation. Abstract :